Potencial prebiótico e antioxidante do cogumelo pleurotus djamor (RUMPH. EX FR.) boedijn sobre a microbiota colônica humana - Andrade, Giuliane Moura (2024)
Edible mushrooms of the genus Pleurotus have gained global prominence for their sensory, nutritional, and functional characteristics. Pleurotus djamor has a high content of bioactive compounds, such as beta-glucans, inulin, and phenolics, which can exert prebiotic and antioxidant activity in the human gastrointestinal tract. The aim of this study was to evaluate the prebiotic and antioxidant properties of P. djamor on the colonic bacterial microbiota during in vitro fermentation. For this purpose, the phenolic compounds of dried P. djamor (PDS) were characterized and quantified using high-performance liquid chromatography, and their antioxidant activity was evaluated using the ABTS, DPPH, and FRAP methods. PDS was subjected to an in vitro gastrointestinal digestion (MUS) and a fermentation process, with 20% added to an assay with human fecal inoculum (40%) and fermentation medium (40%) under anaerobic conditions for 48 hours. Medium with fructooligosaccharides (FOS, 20%) and medium without fermentable substrate (NC) were used as controls. During fermentation, the relative abundance (%RA) of bacterial groups indicative of modulation of the human colonic microbiota was quantified through fluorescence in situ hybridization with multiparametric flow cytometry, and metabolic (pH, quantification of sugars and organic acids) and antioxidant activity were evaluated at 0, 24, and 48 hours, while 1H Nuclear Magnetic Resonance (1H NMR) was used to detect the global metabolic profile at 0 and 48 hours of fermentation. Three independent assays were conducted, expressed as mean ± standard deviation. Ten phenolic compounds (three phenolic acids and seven flavonoids) were identified, with the highest concentrations being epicatechin (3.03 ± 1.54 mg/L), gallic acid (2.71 ± 1.54 mg/L), and quercetin-3-glucoside (2.40 ± 1.54 mg/L). The medium with MUS showed a higher %RA of Lactobacillus spp. - Enterococcus spp. (1.12 ± 0.15 - 4.83 ± 0.32), Bifidobacterium spp. (0.59 ± 0.14 - 1.85 ± 0.37), and Ruminococcus albus - R. flavefaciens (0.37 ± 0.16 - 1.88 ± 0.17) after 48 hours of fermentation. There were no significant changes (p ≥ 0.05) in the %RA of Bacteroides spp. - Prevotella spp. in the medium with MUS, while there was a reduction in the %RA (p < 0.05) of Clostridium histolyticum after 48 hours (2.89 ± 0.17 - 1.22 ± 0.38). The prebiotic index for MUS was positive at 24 and 48 hours, differing significantly (p < 0.05) from NC, indicating prebiotic potential. MUS caused a decrease in pH, sugar consumption, and an increase in the production of organic acids (lactic, acetic, butyric, and propionic acids) in the medium, correlating positively with the bacterial groups whose %RA increased during fermentation. P. djamor showed high antioxidant activity (ABTS 86.94 ± 0.95%; DPPH 36.19 ± 6.71%; FRAP 239.08 ± 33.14 μmol FeSO4/g). This activity persisted during fermentation, but decreased over time. The 1H NMR analysis revealed a distinct profile of essential amino acids in the medium with MUS, not present in the control media. Thus, P. djamor could contribute to beneficial changes in the human colonic microbiota, in addition to having antioxidant activity capable of reducing oxidative stress and promoting intestinal health.